Influence of Heat Treatment and Composition Variations on Microstructure, Hardness, and Wear Resistance of C 18000 Copper Alloy. (11th April 2012) - Osorio-Galicia, Ramon; Gomez-Garcia, Carlos; Alcantara, Miguel Angel; Herrera-Vazquez, Andres
Abstract : The hardness and wear behavior properties of two C 18000 copper alloys with variations in Ni, Si, and Cr concentrations, both within the range of C18000 chemical analysis standard, were studied after the alloy samples had been prepared by melting and casting in sand molds and then heat-treated in solution using two-stage aging for different heating time periods. The results obtained from sample sets of the aforementioned two alloys, C 0 and C 1, show that the alloy C 1, with slightly higher Si and Ni and lower Cr concentrations than the alloy C 0, produced significantly higher hardness values and wear resistance than the alloy C 0 . Optical and electron microscopy microstructure studies of representative samples revealed a copper matrix containing nickel and silicon in solution and precipitates of chromium and nickel silicides. By studying the wear surfaces and debris of the former samples with electron microscopy, different types of wear mechanisms including adhesive, abrasive, oxidation, and repeated-cycle deformation were found. The wear behavior was expressed as mass weight loss, which correspondingly shows a typical inverse relationship with the hardness values for both the C 0 and C 1 alloy groups.